Disruptive selection on plumage coloration across genetically determined morphs. (February 2017) - Grunst, Andrea S.; Grunst, Melissa L.; Rathbun, Nathan A.; Hubbard, Joanna K.; Safran, Rebecca J.; Gonser, Rusty A.; Tuttle, Elaina M.
Abstract : Sexual selection can drive the evolution of conspicuous visual signals that advertise individual quality to prospective mates. Reproductive strategy can influence the balance between selective pressures and whether sexually selected signals evolve. Alternatively, visual signals can serve other functions, including predator deterrence, species recognition and differentiating genetically determined morphs. In the dimorphic white-throated sparrow, Zonotrichia albicollis, we explored how selection on conspicuous coloration changes with reproductive strategy, and whether visual signals of morph identity are discrete from sexually selected signals of individual quality. In this species, white morph birds have more colourful plumage than tan morph birds, and white males are more promiscuous and aggressive than tan counterparts. White females are also more aggressive than tan females. White males with more contrasting coloration achieved higher lifetime fitness, whereas the opposite relationship occurred among tan males. Linear selection gradients indicated strong, positive selection on plumage contrast in white males, but negative selection on contrast in tan males. For both morphs, relationships between female coloration and fitness were weak. Results demonstrate disruptive selection on a visual signalling trait in a colour-polymorphic species and suggest that signals associated with an aggressive morph can also evolve to indicate individual quality within that morph. Highlights: Coloration relates to lifetime fitness in opposite ways in males of two morphs. In an aggressive, promiscuous morph, bright coloration enhances fitness. In a less aggressive, parental morph, bright coloration reduces fitness. Disruptive selection on coloration occurs across males of the two morphs. Colour traits associated with morph identity can also indicate individual quality.